A IMPORTÂNCIA DO DIAGNÓSTICO SITUACIONAL NO CONTEXTO DA RESERVA INDÍGENA NAÔ XOHÃ - Ferreira, Grasiele Cristine; Silva, Dayane Jhenifer Ribeiro; Oliveira, Roberta Ellen Santos; Pereira, Samira Auxiliadora (Sinapse Múltipla, 2020)